Juvenile chronic myeloid leukemia: a case report - Pandey, Praveen Kumar; Singh, Sujeet; Srivastava, Amartya Prakash; Srivastava, Swati; Singh, Nitika; Singh, Shivendra Pratap (International Journal of Research in Medical Sciences, 2024)
Chronic myeloid leukemia (CML) accounts for 2-3% of leukemias in children under 15 and 9% in adolescents aged 15-19. The diagnosis of CML in children, adolescents, and young adults has several differences compared to that in adults. Juvenile myelomonocytic leukemia (JMML)/ juvenile CML is a rare, malignant myelodysplastic/ myeloproliferative neoplasm (MPN) overlap haemopoetic disorder that presents in infants and toddlers and it must be differentiated from other disorders that can show similar presentation in this age group. JMML is very uncommon and the diagnosis is often difficult to establish. The disease has a rapid course and has a median survival of less than 10 months when untreated or undertreated. In this case report we present a case of a 7-year-old male patient with gingival enlargement and swelling along with mobility of mandibular anterior teeth with various associated systemic factors in which various hematological, biochemical, and radiographic investigations were carried out to differentiate CML from other systemic conditions.